Trump Plan for Settlement of Palestine-Israeli Conflict - A. V. Krylov; A. V. Fedorchenko; N. Z. Shuminov (Vestnik MGIMO-Universiteta, 2020)
Abstract: This article is a review of the talk: Peace to Prosperity: A Vision to Improve the Lives of the Palestinian and Israeli People. Washington: The White House, January 29, 2020.181 p.